Physical properties of wild yam (Dioscorea alata) starch treated with chemicals before homogenization and after extraction (2002)
The effect of chemicals applied and methods of application, on the extraction and physical properties of yam (Dioscorea alata genotype BSU 101) starch was investigated. Using a staple wild type yam starch, it was shown that chemicals applied before homogenization (BH) or after starch isolation (ASI) strongly affected starch recovery, color quality, apparent amylose content (AAC) determination, and other physical properties of starch. BH significantly gave lower values than ASI in starch yield, swelling volume (SSV), gelatinization temperature (GT), pasting properties, and gel texture but higher AAC. Similarly, the chemicals used (NaOH, EtOH, EDTA, AgNO3, Na2S2O5, and HgCl2) behaved differently and were influenced by method of application. In BH, AgNO3 gave poor swelling, and low but stable pasting viscosity while HgCl2 gave an interrupted jagged pasting profile attributed to the strong ion hydration. In ASI, Na2S2O5 gave high SSV, lowest GT and stability ratio with high total pasting setback. The high swelling, AAC and pH from EDTA treatment impacted on the pasting properties and gave a rigid gel texture. EtOH and NaOH treatments gave lower Tp and Tc but higher enthalpies. A side reaction of treatments was discoloration of starch from white to dark yellow or red presumably due to some anthocyanins possessing vicinal hydroxyl groups which form complexes with metals. Significant correlations included those between starch yield with pH; AAC with Tp and Tc; SSV with HPV; PV with CPV; HPV with breakdown, stability ratio, setback and breakdown, and gel textures; CPV with To; To with pasting setback and total setback.
Keywords: Yams